(untitled) (Modern education and development, 2025)
The study of blood coagulation mechanisms and their regulation is impossible without the use of laboratory tests. To date, virtually all factors involved in blood coagulation are known. Their primary, secondary and tertiary structures have been discovered. Genes responsible for the formation of these factors have been discovered and deciphered. At the same time, in everyday practice, the study of haemocoagulation in the human body is carried out using laboratory methods, which are not always perfect.